Digital Burnout among Adolescents: The Darker Side of Technology - Kumar, Piyush; Joshi, Ankur; Udayai, Kirti (Journal of Neonatal Surgery, 2025)
An individual’s mental health and well-being are interlinked with all aspects of health — physical, social, and emotional and any compromise in one aspect necessarily has an impact on all others and could act as a barrier to learning and even impact academic performance. However, in the past decade, technology had a huge impact on our overall well-being. Though the benefits offered by the technology could not be ignored, it does have a ‘dark side’ including digital stress- a stress elicited by the confrontation or interaction with, use of, or cognitive orientation toward digital information[i]. It has contributed to a large burden of mental health diseases among adolescents entangled with technology, and undergoing digital burnout. As per the studies, this could affect their mental health impacting the rest of their lifetime due to increased anxiety, depression, sleep disturbances, poor academic performance, and decreased self-esteem, and may contribute to a diminished ability to concentrate, reduced face-to-face social interactions, and impaired overall cognitive functioning. Based on this pressing need to address digital stress, this research paper aims to understand the impact of digital stress on the middle adolescent population, considering its implications for their overall well-being and mental health. Through a comprehensive review of existing literature, this research paper will examine the various sources and manifestations of digital stress experienced by adolescents. The study will also explore the psychological, emotional, and behavioural consequences of digital stress. In the long run, this research aims to develop interventions needed to ensure the long-term psychological and emotional well-being of this middle adolescent population in the digital era.